Melatih Kemahiran Anak Menulis Dongeng Melalui Imajinasi - Prasetyo, Aldi (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2020)
One of the important skills in language learning is writing. Writing skills, need to be familiarized with children, such as fairy tale writing skills. One way to teach it is a fun activity, which is by linking writing with children’s habit’s, which is to teach imagine. This study aims to analyze the results of the implementation of the design of learning to write fairy tales through imagination activities. The method used is descriptive qualitative. The subject is the fourth grade students of MI Muhamadiyah Beji with a total of 14 students. The result showed that 92.85% of the 14 student were able to create fairy tales through the imaginations, and 7.15% of students were unable to write them in writing because they did not follow the learning well. This activity is also able to explore children who have the potential to write.